COMPRESSION THERAPY FOR PELVIC VARICOSE VEINS IN WOMEN - Ivantsok, Volodymyr (Eastern Ukrainian Medical Journal, 2026)
Background. Recommendations support the use of hormonal therapy, analgesics, and venotonics as the first-line treatment, without mentioning compression therapy. However, the use of compression garments may be pathogenetically justified and potentially effective in women with pelvic varicose veins. Materials. We conducted a retrospective study involving 73 women with pelvic varicose veins. All patients underwent compression therapy using second-class compression tights with closed toes (280 DEN) for 30 days without pharmacological support with venotonics, angioprotectors, or antiplatelet agents. The effectiveness of compression therapy was evaluated by comparing the severity of clinical and ultrasonographic findings before treatment and after 30 days. Results. There was a statistically insignificant reduction in reflux in the parametrial veins (p=0.068), uterine veins (p=0.128), gonadal veins (p=0.302), and vulvar veins (p=0.660). However, there was a statistically significant reduction in chronic pelvic pain (p=0.001), dyspareunia (p=0.001), and hypogastric discomfort (p=0.002). The likelihood of being free from chronic pelvic pain following compression therapy was 90%, with the proportion of such patients increasing from 16.4% to 67.1% (OR 10.38; CI 4.72–22.83; 95%; p=0.001). The frequency of mild pain (1–3 points) decreased to 6.8% from 28.8% (OR 0.18; CI 0.06–0.52; 95%; p=0.001), moderate pain (5–7 points) decreased to 20.5% from 37.0% (OR 0.44; CI 0.21–0.92; 95%; p=0.044), and severe pain (8–10 points) decreased to 5.5% from 17.8% (OR 0.27; CI 0.08–0.86; 95%; p=0.039). Conclusion. Compression therapy for pelvic varicose veins may be considered as a first-line treatment option. The use of second-class compression tights with closed toes (280 DEN) for 30 days resulted in a statistically insignificant (p>0.05) reduction in reflux in the parametrial and uterine veins. However, there was a statistically significant reduction in clinical manifestations, including chronic pelvic pain (p=0.001), dyspareunia (p=0.001), and copulative discomfort (p=0.002).